Tractates Peah and Demay - Guggenheimer, Heinrich W. (Studia Judaica, 2000)
Tractate Peah and Demay is the second volume in the edition of the Jerusalem Talmud, a basic work in Jewish Patristic. It presents basic Jewish texts on the organization of private and public charity, and on the modalities of coexistence of the ritually observant and the non-observant. This part of the Jerusalem Talmud has almost no counterpart in the Babylonian Talmud. Its study is prerequisite for an understanding of the relevant rules of Jewish tradition.